Evaluation of radiofrequency exposure levels from multiple wireless installations in population dense areas in Korea. Issue 8 (4th September 2014) - Kim, Byung Chan; Kim, Wan‐Ki; Lee, Gi‐Tae; Choi, Hyung‐Do; Kim, Nam; Pack, Jeong‐Ki
<x xml:space="preserve">Abstract</x> This paper presents the results of measurements from simultaneous human exposure to various radiofrequency (RF) signals at densely populated areas. Measurements were performed at 1260 positions across Korea to determine exposure compliance to electromagnetic fields for the general public. The measured exposure levels were very low compared with the international exposure guidelines and Korean human protection notice. The highest total exposure ratio was 5.1 × 10−3 (approximately 7.1% of guideline limits). Bioelectromagnetics 35:603–606, 2014. © 2014 Wiley Periodicals, Inc.